The Concept of Neo-History And The Opinion of Urdu Critics - Muhammad Akbar Ali; Dr. Aqeela Basheer (Zaban-o-Adab, 2022)
New Historicism is a school of literary theory, It was created by American critic Stephen Greenblatt It was present in 1950,as a name of "Cultural poetics" but this theory was developed in 1980,New historicism represents the literature in the cultural content and also we can examine the work which is affected by writer’s time. Michel Foucault aims at interpreting a literary text as an expression of or reaction to the power structures of the surrounding society. He also tells us how has the event been interpreted? There are some hidden corners which are presented by New Historicism colonization facts, Feminism Theory and power role in society decisions. This all concerns with the social knowledge of society but in literature it investigates the life of author, the social rules found within a text and reflection of a work’s historical situation in the text. Such type of picture is present in the work of Dr. Iqbal Afaqi, Nasir Abbas Nayyar and Prof. Atteq ullah etc.